The Influence of Promotion on Consumer Purchase Interest Using the TQM (Total Quality Management) Method at Almeera Mobile & Acc Store - Muhammad Seftian Hasibuan; Marwan Marwan (Industrial Engineering System and Management Journal, 2025)
Almeera Ponsel & ACC Store is a store that sells mobile phones, starter cards and internet vouchers, mobile phone accessories, credit top-ups and electricity tokens and other equipment. The current condition of the store is experiencing ups and downs in sales, because many consumers visit but do not end up buying products at the store for various reasons. Researchers use the TQM (Total Quality Management) method to overcome problems in the store and improve promotions carried out by the store, and the quality of employee performance, in order to be able to increase consumer purchasing interest. The data analysis method used by the researcher is the descriptive analysis method and the analysis method of the level of influence of promotion on consumer purchasing interest or purchasing decisions in the application of TQM (Total Quality Management), namely the comparison of store service performance scores with consumer expectation scores. In the calculation results of the average initial state of the consumer purchasing decision attribute for store service performance, the average result is at a level less than 3, thus the consumer purchasing decision in terms of store service performance is at an unsatisfied level because it is not comparable to the average results of consumer expectations at a level greater than 3, while in the calculation results of the average implementation of TQM (Total Quality Management), the consumer purchasing decision attribute for store service performance gets an average result at a level greater than 3, thus the consumer purchasing decision in terms of store service performance is at a satisfied level because it is comparable to the average results of consumer expectations at a level greater than 3, thus the TQM (Total Quality Management) method has an effect on increasing consumer purchasing interest.